Interface engineering of Cu(In, Ga)Se2 and atomic layer deposited Zn(O, S) heterojunctions. (24th July 2017) - Schmidt, Sebastian S.; Merdes, Saoussen; Steigert, Alexander; Klenk, Reiner; Kaufmann, Christian A.; Sanli, Ekin Simsek; van Aken, Peter A.; Oertel, Mike; Schneikart, Anja; Dimmler, Bernhard; Schlatmann, Rutger
Abstract: Atomic layer deposition of Zn(O, S) is an attractive dry and Cd-free process for the preparation of buffer layers for chalcopyrite solar modules. As we previously reported, excellent cell and module efficiencies were achieved using absorbers from industrial pilot production. These absorbers were grown using a selenization/sulfurization process. In this contribution we report on the interface engineering required to adapt the process to sulfur-free multi source evaporated absorbers. Different approaches to a local sulfur enrichment at the heterojunction have been studied by using surface analysis (XPS) and scanning transmission electron microscopy. We correlate the microstructure and element distribution at the interface with device properties obtained by electronic characterization. The optimized completely dry process yields cell efficiencies >16% and 30 × 30 cm 2 minimodule efficiencies of up to 13.9% on industrial substrates. Any degradation observed in the dry heat stress test is fully reversible after light soaking.